Development of Vaccine Candidates Against Mycobacterium Tuberculosis in 2019-2023 - Jongga Adiyaksa; Fithriyah Sjatha (Malahayati Nursing Journal, 2024)
ABSTRACT With extensive use of the Bacillus Calmette–Guérin (BCG) vaccine, the global prevalence of Mycobacterium tuberculosis (MTB) remains. A number of vaccines proposed to cure and prevent tuberculosis (TB) infection are undergoing various stages of clinical trials. Although vaccine production is progressing, more attention is needed. A number of TB vaccines are currently undergoing clinical trials, most of which rely on a combination of proteins and/or adjuvants or recombinant viral vectors specific for MTB antigens. We tried to cover the range of TB vaccines in this study by analyzing their composition, the immunological responses they elicit, and the stages of clinical trials. To find out the Development Of Prospective Vaccines Against Mycobacterium Tuberculosis. This research uses a literature review, between August 2023 and November 2023, the authors of this literature review checked PubMed, Science Direct, Google Scholar, and other databases containing research findings or scientific articles. Only studies that met the above search criteria were included in the systematic review. Many recently developed tuberculosis vaccines are reportedly in the final stages of clinical trials, where they have significantly strengthened the immune system and even produced protection against the host. Immunization produced by vaccines that have successfully passed the initial stages of clinical trials is safe and effective, and can even surpass BCG in terms of immunity.  Based on the description above, it can be concluded that many recently developed tuberculosis vaccines are reported to be in the final stages of clinical trials, where they have significantly strengthened the immune system and even produced protection against the host. Immunization produced by vaccines that have successfully passed the initial stages of clinical trials is safe and effective, and can even surpass BCG in terms of immunity. With the development of new TB vaccines that strengthen the body's immunity and create effective delivery mechanisms, hopes for TB treatment and prevention are increasing. The development of vaccine effects can be facilitated, in part, through the use of effective delivery mechanisms, which have also been used in TB vaccines. Keywords: Tuberculosis, Vaccine, Bacteria, Mycobacterium Tuberculosis, BCG